PENGARUH METODE LATIHAN DAN SPORTIFITAS TERHADAP KETERAMPILAN PASING ATAS (Studi Eksprimen pada Mata Pelajaran Penjaskes Materi Bola Voli Siswa Kelas VI Sekolah Dasar Negeri 35 Pagar Alam) - Rori Yansyah (DIADIK, 2021)
This study aims to ditermine the diffirences in training methods on the level of students sportsmanship towards upper passing skill. The methods in this research is 2x2 factorial with pretest and posttest. The population in the study were students 35 natural fence elementary schools. The research sampel consisted of 60 students. 30 students in the exprerimental group with high sportsmanship and 30 students in the control group with low sportsmanship. this study was condukted for 2 month simultaneously in each group. The instrument in this study was a test (pretest dan posttest) to pass over for 3 minutes. In addition, instrument  are also used in the form of observations to assess student sportsmanship. Based on pre-test data processing and final test. The statistics used for data analysis in hypothetical research with t-test statistics. Then the results show tcount = 7,91 > ttable = 1,771. Thus there is a significant difference between the experimental group who has high sportsmanship following the top passing practice in pairs and the control group with low sportsmanship following top pass practice to the wall. Based on the results of observational data processing, it is that sportsmanship towards training methods can improve volleyball passing skills